2019
DOI: 10.1371/journal.pone.0218247
|View full text |Cite
|
Sign up to set email alerts
|

The Park Prescription Study: Development of a community-based physical activity intervention for a multi-ethnic Asian population

Abstract: This mixed-methods study aims to inform the development of a ‘Park Prescription’ intervention, including face-to-face counseling on physical activity and park use and providing weekly structured exercise sessions in the park to promote physical activity. Participants aged 40–65 years were recruited from regional health screening events in Singapore where they completed a questionnaire (N = 97) and consented to focus group (FG) participation (N = 16). The questionnaire assessed current park use, and the type, d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 57 publications
2
29
0
Order By: Relevance
“…At the time of the study, health screenings took place across the entire city and participants for the present RCT were recruited from screenings conducted by a large hospital with a catchment population in the northern part of Singapore. Health screenings, together with the recruitment process to our study, had been previously described in detail [32,33]. Briefly, screening events followed a systematic approach at common community outdoor open spaces or community centers, followed by separate sessions during which residents picked-up their health report.…”
Section: Study Design and Participantsmentioning
confidence: 99%
See 2 more Smart Citations
“…At the time of the study, health screenings took place across the entire city and participants for the present RCT were recruited from screenings conducted by a large hospital with a catchment population in the northern part of Singapore. Health screenings, together with the recruitment process to our study, had been previously described in detail [32,33]. Briefly, screening events followed a systematic approach at common community outdoor open spaces or community centers, followed by separate sessions during which residents picked-up their health report.…”
Section: Study Design and Participantsmentioning
confidence: 99%
“…Due to its greenery and easy access to parks and green spaces it is also referred to 'a city in a garden' [30,31]. However, research has shown that 63% of Singaporeans visit parks and green spaces only twice per month or even less and few reported to engage in active sports in parks [32]. The Singapore context creates an opportunity to explore the application of the novel and increasingly popular approach of Park Prescription to the general population.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…themes being repeated to a point where no new themes emerge) may not have been achieved. However, for most of the research questions it was only appropriate to engage these participants, they provided valuable insights and some of these were consistent with FGD feedback from the formative research that was conducted to develop the intervention (30).…”
Section: Strengths and Limitations Of The Process Evaluationmentioning
confidence: 78%
“…They discussed being motivated by the intervention to do this in their own time. The formative research conducted to develop the PPI also found, that the target population of the intervention appeared to have a preference for shorter and less intense exercise (30). A population survey of 1,332 adults (response rate 46%) selected randomly from an Australian electoral role, which included questions on participants' preferences for structured versus unstructured PA found that 53% reported enjoyment of unstructured PA and 31% reported high enjoyment of structured PA.…”
Section: Did a Higher Level Of Group Exercise Participation Corresponmentioning
confidence: 99%